Topics on Applied Basic Theory Research of 23Co14Ni12Cr3MoE(A-100)Steel - LI Zhi (Journal of Aeronautical Materials, 2017)
The basic features of A-100 steel, such as relationship between cogging process and mechanical properties, relationship among the forging process, grain size and mechanical properties, secondary hardening, and fatigue properties were discussed. The high-temperature homogenization and high deformation at first step technique were developed on the foundation of multiple upsetting and stretching, high forging ratio technique used for 300M steel, and became the technique foundation of cogging process in A-100 steel. The fracture toughness of A-100 steel was tended to be influenced by hot working process. The grain size grew heavily, and mixed grain structure was appeared after heating at 1140℃ and above with deformation amount below 20%, the fracture toughness was also decreased. The secondary hardening performance of A-100 steel was changed after the deformation at low temperature. The tensile strength peak temperature was changed to 468℃,the tensile strength was decreased slowly when over aging. A-100 steel was cyclic hardened, and its fatigue crack growth properties were better than 300M steel. The high cycle fatigue property was heavily deteriorated when tested in 3.5%NaCl solution.